(untitled) (Scripta : English Department Journal, 2026)
This study aims to examine students’ perceptions of AI-Powered Writing Assistants, namely Grammarly, ChatGPT, and QuillBot, regarding their ability to enhance writing skills at STKIP Muhammadiyah Pagar Alam. The rapid development of Artificial Intelligence has significantly influenced educational practices, particularly in academic writing, by providing tools that support grammar correction, idea generation, and paraphrasing. This study employed a descriptive quantitative research design. The participants consisted of 112 students from the English Education Study program, selected using a total sampling. Data were collected through a structured questionnaire using a four-point Likert scale and analyzed using descriptive statistics. The findings indicate that students generally have positive perceptions of AI-powered writing assistants. These tools are considered helpful in improving grammar accuracy, generating ideas, organizing writing, and enhancing overall writing quality. However, the results also reveal concerns regarding students’ dependence on AI tools, a potential reduction in critical thinking, and academic risk related to misuse. Despite these concerns, students demonstrate awareness of academic ethics and the importance of responsible use. In conclusion, an AI-Powered Writing Assistant plays a significant role in supporting students’ writing development when used appropriately. Therefore, balanced and ethical use of these tools is essential to maximize their benefits while minimizing potential risk in academic writing.